Enhancing science teacher performance: The role of interpersonal communication, pedagogical competence, and organizational climate - Iwan wijiyanto; Rina Mida Hayati (Journal of Education Policy and Management Studies, 2025)
The purpose of this study in general was to analyze the contribution of interpersonal communication, pedagogical competence and organizational climate to the performance of science subject teachers Specifically, the objectives of this study are as follows: (1) To analyze the contribution of interpersonal communication, pedagogical competence and organizational climate simultaneously to the performance of science subject teachers; (2) To analyze the contribution of interpersonal communication to the performance of science subject teachers; (3) To analyze the contribution of pedagogic competence to the performance of science subject teachers; and (4) To analyze the contribution of organizational climate to the performance of science subject teachers.The approach of this research was quantitative. The independent variables in this study were intepersonal communication, pedagogic competence, and organizational climate, while the dependent variable was teacher performance. This study was conducted on science teachers at MTs in Purworejo District. The population of this study were all science subject teachers in public and private MTs in Purworejo District, which numbered 38 people. The sample in this study were all science teachers in MTs in Purworejo District, which totaled 38 people. Thus, this study uses saturated samples. Data collection techniques using a questionnaire. The analysis used was multiple linear regression analysis.Based on the results of data analysis, it can be concluded that: (1) Interpersonal communication, pedagogical competence and organizational climate contribute positively to the performance of science subject teachers. (2) Interpersonal communication demonstrated a statistically significant positive contribution to the performance of science subject teachers. (2) Pedagogical competencies contribute positively to the performance of science subject teachers. (3) The organizational climate demonstrated a statistically significant positive contribution to the performance of science subject teachers.